Cameroon - Transport Sector Reform - Reja, Binyam (World Bank, Washington, DC, 2012)
The note briefly outlines the impacts, and lessons of the Transport Sector Reform Project in Cameroon, whose objectives aimed at developing private participation, and continue the restructuring of transport sector utilities. While some activities, such as railway operations are being partly privatized, through concession arrangements, and bus companies liquidated, allowing liberalization of urban transport, efforts at reforming the port sector, will continue under the Third Structural Adjustment Credit. However, the privatization of the civil aviation company did not take place, and, efforts to improve the international transit system were only partially achieved. Lessons point at the need to address the budgetary, and social impact of privatization, including severance payments, early on during project preparation; the crucial aspect for higher level management - Government and donors - to be committed to, and involved in the process of reform implementation; the essential need for Bank continuity in supporting the country strategy, through successive projects that will prod reforms, and consolidate those achieved through the project, emphasizing financial management issues.